Integration of information and communication technology in mathematics teaching in Metro Manila public secondary schools - Cajilig, Norma Gloria
This is an investigation on the adoption patterns of Metro Manila public secondary school teachers while information and communication technology (ICT) is being integrated into their teaching. Evidence shows that the majority of the teachers had highly favorable attitudes toward the use of new technologies in instruction. This disposition was brought about, among other things, by the influence of authority and/or the status individuals normally attach to technology innovation. This study further shows that while the enthusiasm level for integration was high, the extent of ICT implementation was poor mainly due to the lack of computer facilities and teacher training programs. It is recommended that the government take advantage of the teachers? enthusiasm by providing the teachers with necessary tools and opportunities to improve their teaching.
Keywords: High school teachers -- Training of -- Philippines -- Manila Metropolitan Area; High school teachers -- Philippines -- Manila Metropolitan Area -- Attitudes; Mathematics -- Study and teaching (Secondary) -- Philippines -- Manila Metropolitan Area; Information technology -- Philippines -- Manila Metropolitan Area; Telecommunication -- Philippines -- Manila Metropolitan Area; Teaching -- Philippines -- Manila Metropolitan Area -- Aids and devices